2002
DOI: 10.1007/s00106-001-0619-z
|View full text |Cite
|
Sign up to set email alerts
|

Morphologische und funktionelle Ergebnisse der Knorpelpalisadentympanoplastik

Abstract: The low rate of recurrent tympanic membrane defects (2.4%) shows that palisade cartilage tympanoplasty is particularly appropriate for the management of difficult indications in middle ear surgery. Further, it could be demonstrated that the PCT can be combined safely with titanium ossicular reconstruction prostheses. Regarding postoperative hearing results the negative preselection of pathological conditions has to be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Complications rates and long-term failure rates appear statistically and clinically comparable to tympanoplasty using temporalis fascia with no difference in the odds ratio of the two groups based on meta-analysis (0.89, 95% CI: 0.62 to 1.30). While this systematic review specifically excluded studies that reported results of palisade cartilage tympanoplasty combined with other procedures, an overall graft take rate of >97% has been reported in patients with who underwent combined palisade tympanoplasty with mastoidectomy for pathologies such as as cholesteatoma, adhesive otitis, and chronic mucosal disease [13, 18]. Our results are consistent with previous systematic reviews that demonstrate superior graft integration rate with cartilage tympanoplasty compared to temporalis fascia [8, 19].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Complications rates and long-term failure rates appear statistically and clinically comparable to tympanoplasty using temporalis fascia with no difference in the odds ratio of the two groups based on meta-analysis (0.89, 95% CI: 0.62 to 1.30). While this systematic review specifically excluded studies that reported results of palisade cartilage tympanoplasty combined with other procedures, an overall graft take rate of >97% has been reported in patients with who underwent combined palisade tympanoplasty with mastoidectomy for pathologies such as as cholesteatoma, adhesive otitis, and chronic mucosal disease [13, 18]. Our results are consistent with previous systematic reviews that demonstrate superior graft integration rate with cartilage tympanoplasty compared to temporalis fascia [8, 19].…”
Section: Discussionsupporting
confidence: 88%
“…Specifically, only studies reporting hearing outcomes beyond 6 months were included. In addition to strict inclusion and exclusion criteria, the quality of studies were further assessed by grading their level of evidence based on the Oxford Centre for Evidence-Based Medicine Levels of Evidence for Therapy Studies [13]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation